Taṭawwur al-Ta‘līm al-‘Alī bi Indūnīsī - HS., Mastuki (Studia Islamika, 1997)
Indonesian HIgher Institution of Islamic Learning (Perguruan Tinggi Islam-PTI) was born out of Islamis struggle  which started from the end the Dutch colonial period. The struggle itself was tringgered by the fact that in the 1930s the colonial goverment only established a Technical school (Technische Hoogeschool), a Law School (Rechts Hoogeschool) and a medical school (Geneeskundige Hoggeschool) at tertiary level.DOI: 10.15408/sdi.v4i3.775